Effect of growth regulators on yield and quality of Sahebi grape (Vitis vinifera) under temperate conditions - KHALIL, AROOSA; SHARMA, M K; KUMAR, AMIT; NAZIR, NOWSHEEN; JAVEED, KOUSAR (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted during 2015–16 at the research farm of Sher-e-Kashmir University of Agricultural Sciences and Technology of Kashmir, Shalimar Campus, Srinagar, Jammu and Kashmir to see the effect of growth regulators on yield and quality of 23 years old Sahebi grape (Vitis vinifera L.). The experiment comprised of 9 treatments with 2 growth regulators, viz. GA3 (20 and 40 ppm), 6-BA (10 and 20 ppm) and their combinations were sprayed at 3 stages, viz. S1, pre-bloom (single spray); S2, 3–4 mm berry size (single spray); S3, pre-bloom + 3–4 mm berry size (double superimposed spray) were replicated thrice in randomized block design (RBD). Observations were recorded on berry yield, bunch and physico-chemical characteristics. Application of GA3 @40 ppm + 6-BA @10 ppm at pre-bloom + 3–4 mm berry size (double superimposed spray) stage resulted in highest berry yield, bunch weight, bunch length and total sugars followed by treatment G6S3 during both the years, however treatment G8S3 recorded significantly higher bunch diameter, berry length, berry weight, total soluble solids, TSS/acid ratio and juice content. The interaction studies had no influence on berry diameter, acidity, ascorbic acid and anthocyanin content.